Nitrogen dynamics within and between decomposing leaves, bark and branches in Eucalyptus planted forests. (October 2016) - Versini, Antoine; Laclau, Jean-Paul; Mareschal, Louis; Plassard, Claude; Diamesso, Leki Alpiche; Ranger, Jacques; Zeller, Bernd
Abstract: Nitrogen transfer between litter components is often presented as a key mechanism responsible for the synergistic effect of litter mixtures on decomposition rates. The litter cover is a heterogeneous environment stemming from the input of chemically distinct materials and the transfer of nutrients in this patchy environment is likely to fulfil the specific needs of microbial communities in each micro-environment. Our study aimed to gain insight into the factors controlling N dynamics within and between leaves and woody components in the litter cover. We used 15 N labelling to discriminate endogenous and exogenous N and to measure N transfers between three types of litter components, viz. leaves and twigs (L + T), bark and branches, in 162 litter bags for more than 2 years in two Congolese Eucalyptus forests with contrasting N status (low-N vs high-N litter). Large quantities of N were released from N-rich L + T at the end of the study while early release of leachable N was only observed for the high-N L + T. Exogenous N was only incorporated in N-poor litter components (bark and branches) and a net increase in N compared to the initial quantities only occurred in the low-N bark. The bi-directional N transfers observed between litter components were most likely microbially-mediated rather than driven by abiotic leaching. Nitrogen transfers were controlled by the N status of both source and sink litter components, contrary to the diffusion theory based on concentration gradient. For a given source, more N was transferred to N-rich than to N-poor sink components. Our results suggested that the microbial community might control both the quantity of N available to be transferred to other microsites and the quantity that is actually transferred, presumably because the potential for N immobilization may be limited in N-poor litter components. Interactions among micro-environments can favor chemical convergence from distinct litter components to humified organic matter along the decay continuum. Highlights: 15 N labelling was used to investigate N dynamics within and between litter components. N transfers were most likely microbial-mediated rather than driven by leaching. N transfers were controlled by the N status of both source and sink components. N transfers promoted chemical convergence of litter components along the decay continuum.